2023
DOI: 10.1038/s41597-022-01899-x
|View full text |Cite|
|
Sign up to set email alerts
|

MIMIC-IV, a freely accessible electronic health record dataset

Abstract: Digital data collection during routine clinical practice is now ubiquitous within hospitals. The data contains valuable information on the care of patients and their response to treatments, offering exciting opportunities for research. Typically, data are stored within archival systems that are not intended to support research. These systems are often inaccessible to researchers and structured for optimal storage, rather than interpretability and analysis. Here we present MIMIC-IV, a publicly available databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
318
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 579 publications
(456 citation statements)
references
References 21 publications
0
318
0
Order By: Relevance
“…Data were collected from two large open critical care databases, the Medical Information Mart for Intensive Care III (MIMIC III) and MIMIC IV. MIMIC IV, which includes ICU patients treated at Beth Israel Deaconess Medical Center from 2008 to 2019, was employed to examine the relationship between LAR at admission and mortality in ICU patients with AKI [ 17 ]. MIMIC III, which contains data from 2001 to 2012, was carried out to validate the results [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were collected from two large open critical care databases, the Medical Information Mart for Intensive Care III (MIMIC III) and MIMIC IV. MIMIC IV, which includes ICU patients treated at Beth Israel Deaconess Medical Center from 2008 to 2019, was employed to examine the relationship between LAR at admission and mortality in ICU patients with AKI [ 17 ]. MIMIC III, which contains data from 2001 to 2012, was carried out to validate the results [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…MIMIC IV, which includes ICU patients treated at Beth Israel Deaconess Medical Center from 2008 to 2019, was employed to examine the relationship between LAR at admission and mortality in ICU patients with AKI [ 17 ]. MIMIC III, which contains data from 2001 to 2012, was carried out to validate the results [ 17 ]. The authors were entitled to extract data from the two databases after completion of the course "Protecting Human Research Participants".…”
Section: Methodsmentioning
confidence: 99%
“…The data in this retrospective study were extracted from the MIMIC IV (Johnson et al, 2021), which is an extensive, freelyavailable database comprising de-identified health-related data from patients who were admitted to a tertiary academic medical center in Boston, MA, USA. It contains information between 2008-2019 for each patient while they were in the hospital: laboratory measurements, medications administered, vital signs documented, and so on.…”
Section: Data Sourcementioning
confidence: 99%
“…All subjects' data were extracted from two large critical-care medical databases, which are free and open to researchers from all over the world. Data of the training cohort were collected from the Multiparameter Intelligent Monitoring in Intensive Care IV (MIMIC-IV; version 2.0) database (18,19), which is jointly developed and run by the Massachusetts Institute of Technology (Cambridge, MA, USA) and the Beth Israel Deaconess Medical Center (BIDM, Boston, MA, USA). This database contains the detailed and comprehensive clinical data of about 250,000 patients admitted to the intensive care unit (ICU) and emergency unit of the Beth Israel Deaconess Medical Center from 2008 to 2019, including demography, laboratory tests, documented vital signs, medications administered, and so on.…”
Section: Data Sourcesmentioning
confidence: 99%